Foamed geopolymer with customized pore structure - Balczár Ida; Boros Adrienn; Kovács András; Korim Tamás (Chemical Industry and Chemical Engineering Quarterly, 2022)
Due to their favorable production conditions and promising properties (e.g., low shrinkage after foaming, mechanical and chemical stability, high-temperature resistance), geopolymer foams are suitable for heat- and sound insulating refractory building materials. Another promising field of application may be their use as catalyst supports in water treatment. Metakaolin-based foams were prepared by a direct foaming process with high total porosity (> 75 vol%), low bulk density (< 500 kg/m3), approximately 1 MPa compressive strength, and low thermal conductivity (0.095 W/mK). By varying the concentration of foaming agent (H2O2 solution) and stabilizing agent (sodium oleate), it is possible to produce foams with designed porosity and pore size distribution. Foams with mainly closed pores are suitable for thermal insulation, while those with significantly open pores can use as catalyst supports. The computed tomography images showed that the concentration of stabilizing agent is a key parameter in forming a homogeneous pore structure and open pores; up to 24 vol% open porosity can be achieved without significantly affecting other properties. The physical properties of the foams are equally influenced by the thickness of cell walls and the size of the cells themselves.